Machiavelli's children : - Samuels, Richard J. (Cornell University Press, 2003)
Two late-developing nations, Japan and Italy, similarly obsessed with achieving modernity and with joining the ranks of the great powers, have traveled parallel courses with very different national identities. In this audacious book about leadership and historical choices, Richard J. Samuels emphasizes the role of human ingenuity in political change. He draws on interviews and archival research in a fascinating series of paired biographies of political and business leaders from Italy and Japan.